PENERAPAN SANKSI ADAT DEDOSAN DALAM AWIG-AWIG BANJAR PEGOK DESA ADAT SESETAN - Widnyana, I Made Adi; Tagel, Dewa Putu (VYAVAHARA DUTA, 2019)
In Bali, the existence of customary law is still stable and sustainable until now and it is very easy to find it in some areas that still maintain the lives of indigenous people through the institution of customary villages or villages. Traditional law dibali generally include; awig, awig, perarem, eka elikita, and other customary rules. In carrying out customary rules, there are customary sanctions that will be imposed on violators of customary rules. These customarysanctions are of various kinds and are different in each customary area in Bali.Dedosan sanction is an example of one of the sanctions that exist in customary rules. As applied in banjar pegok through banjar awig-awig adat which makes dedosan sanctions as an alternative in minimizing losses arising from the negligence of customary manners in carrying out customary obligations, so that the activities of manners customs that are preoccupied with matters outside the customs, do not interfere with the development of traditional traditions thatare still ongoing. Although the application of customary sanctions has begun to be more flexible in the present, it should still be carried out firmly and clearly, so that it does not cause jealousy and does not accustom customary manners to carry out dedosan sanctions just to avoid adat activities. So that if this is allowed to continue then it will certainly also affect the existence of adat thatprevails in an area.